Astragaloside IV Alleviates Cerebral Ischemia-Reperfusion Injury through NLRP3 Inflammasome-Mediated Pyroptosis Inhibition via Activating Nrf2. (30th December 2021) - Xiao, Lan; Dai, Ziwei; Tang, Wenjing; Liu, Canwen; Tang, Biao
Abstract : As one of the fundamental components of Astragalus membranaceus, astragaloside IV (AST IV) exerts protective effects against cerebral ischemia-reperfusion injury (CIRI). Nevertheless, the underlying mechanisms have not yet been conclusively elucidated. To do so, here, we report on the regulatory effects of Nrf2 on NLRP3 inflammasome-mediated pyroptosis. CIRI was induced by middle cerebral artery occlusion-reperfusion (MCAO/R) in Sprague Dawley rats and modeled by oxygen and glucose deprivation/reoxygenation (OGD/R) in SH-SY5Y cells. Cerebral infarct volume and neurological deficit score served as indices to evaluate MCAO/R injury. In addition, the CCK-8 assay was used to assess cell viability, the LDH leakage rate was used as a quantitative index, and propidium iodide (PI) staining was used to visualize cells after OGD/R injury. The NLRP3/Caspase-1/GSDMD pathway, which produces the pores in the cell membrane that are central to the pyroptosis process, was assessed to investigate pyroptosis. Nrf2 activation was assessed by detecting Nrf2 protein levels and immunofluorescence analysis. We show that after MCAO/R of rats, the infarct volume and neurological deficit score of rats were strongly increased, and after OGD/R of cell cultures, cell viability was strongly decreased, and the LDH leakage rate and the proportion of PI-positive cells were strongly increased. In turn, MCAO/R and OGD/R enhanced the protein levels of NLRP3, Caspase-1, IL-1 β, GSDMD, and GSDMD-N. Moreover, Nrf2 protein levels increased, and Nrf2 translocation was promoted after CIRI. Interestingly, AST IV (i) reduced the cerebral infarct volume and the neurological deficit score in vivo and (ii) increased the cell viability and reduced the LDH leakage rate and the proportion of PI-positive cells in vitro. AST IV reduced the protein levels of NLRP3, Caspase-1, IL-1 β, GSDMD, and GSDMD-N, inhibiting NLRP3 inflammasome-mediated pyroptosis. AST IV also increased the protein levels of Nrf2 and promoted the transfer of Nrf2 to the nucleus, accelerating Nrf2 activation. Particularly revealing was that the Nrf2 inhibitor ML385 partly blocked the above effects of AST IV. Taken together, these results demonstrate that AST IV alleviates CIRI through inhibiting NLRP3 inflammasome-mediated pyroptosis via activating Nrf2.